L’activité des enseignants de la conduite entre gestion de l’environnement et enseignement de la conduite automobile : une revue de questions - Sarah Belouahchi; Camille Sagnier; Emilie Loup-Escande (Activités, 2023)
This paper proposes a review of driving instructor activity. Firstly, we present the most relevant characteristics of the road space environment, where driving instructors carry out their activity. We explain that this environment is dynamic, due to unpredictable changes in situation. It is also risky, due to the presence of numerous risk factors, and diverse, depending on the configuration of the roads, and finally, it is shared with other road users. Secondly, we try to identify the actual tasks of driving instructors and their characteristics during a driving session. The sharing of the road space leads them to organize their activity into two tasks. The first relates to safe management of the environment and includes the driving of the vehicle. The second concerns the driving instruction, which includes pedagogical guidance. Thirdly, we deal with the actual activity that the instructor carries out to complete his/her dual task. Two strategies emerge. The first concerns the instructor’s selection of the road zones that will be proposed to the student. The second concerns variations in the instructor’s guiding activity. We will show that these strategies reflect a formative dimension for the instructor, whose activity is personalised in accordance with the student’s level, the detection of his/her difficulties and the modification of learning situations. Finally, we conclude with a presentation of the driver instruction curriculum and the instructor’s training programme. These are accompanied by a difficulty of operationalisation by the instructor in a situation with the student.